Babies under 1 year with atypical development: Perspectives for preventive individuation and treatment - Ferrara, Rosaria; Iovino, Leonardo; Di Renzo, Magda; Ricci, Pasquale (Frontiers in Psychology, 2022)
A baby’s first year of life is a time of immense development and cerebral plasticity. Following today’s research and clinical observation, the period of the first year of life provides a new challenge inasmuch it is presently clear that it is possible to identify developmental anomalies in this window of time. Effecting early screening procedures could prove very useful, especially where we find genetic vulnerabilities in brothers and sisters of autistic subjects. Interventions of this kind, already practiced by some Public Health systems, can mean taking early action and primary protective measures with significant impacts not only on the subjects (babies and family members) concerned, but also on the public purse. It is, therefore, essential to provide for specific professionalized procedures for psychologists, pediatricians and neuropsychologists to be introduced through personnel highly specialized in interventions during the first year of life.